2021
DOI: 10.1016/j.jep.2021.114098
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of the potential mechanism of a preventive Chinese medicine formula on coronavirus disease 2019

Abstract: Ethnopharmacological relevance With the spread of Coronavirus Disease (2019) (COVID-19), combination with traditional Chinese medicine (TCM) has been widely used as a prevention and therapy strategy in China. Xin guan No.1 (XG-1) prescription is a preventive formula recommended by the Hunan Provincial Administration of TCM to prevent the pandemic of COVID-19. Aim of the study To explore the potential preventive mechanisms of XG-1 against COVID-19 in the combination of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
(45 reference statements)
1
6
0
Order By: Relevance
“…Typical flavonoids including quercetin and luteolin were found in honeysuckle extracts (Table ). The existence of these compounds and the effects of honeysuckle extracts in inhibiting the interaction between the spike protein of SARS-CoV-2 and ACE2 could be supported by previous computational molecular docking studies that suggest these bioactive flavonoids might have potential COVID-19 related inhibition . In addition, other extracts of botanical herbs, such as the ethanol and water extracts of cloves, were shown to inhibit the binding between the SARS-CoV-2 spike protein and ACE2, which is consistent with our observations in the present study. , These observations indicated that honeysuckle extracts, especially the ethanol extract, might show remarkable anti-COVID-19 effects by blocking the interaction between the SARS-CoV-2 spike protein and ACE2.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Typical flavonoids including quercetin and luteolin were found in honeysuckle extracts (Table ). The existence of these compounds and the effects of honeysuckle extracts in inhibiting the interaction between the spike protein of SARS-CoV-2 and ACE2 could be supported by previous computational molecular docking studies that suggest these bioactive flavonoids might have potential COVID-19 related inhibition . In addition, other extracts of botanical herbs, such as the ethanol and water extracts of cloves, were shown to inhibit the binding between the SARS-CoV-2 spike protein and ACE2, which is consistent with our observations in the present study. , These observations indicated that honeysuckle extracts, especially the ethanol extract, might show remarkable anti-COVID-19 effects by blocking the interaction between the SARS-CoV-2 spike protein and ACE2.…”
Section: Resultssupporting
confidence: 92%
“…The relative ion intensity of each identified compound is shown in Table 1. Sesamoside (6), loganic acid (8), secologanic acid (9), 4-caffeoylquinic acid (10) and kaempferol (27) were the five major compounds in the water extract (Table 1), whereas luteolin (28), colossolactone E (31), salvigenin (32), atractylon (35) and zerumbone (36) were the major compounds in the ethanol extract (Table 1). 3-Caffeoylquinic acid (7) and capparoside A (15) were the two major compounds in both water and ethanol extracts.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of rutinum is shown in Figure 4d . In China’s drug intervention program against COVID‐19, prescription XG‐1 has shown good treatment effects (Wu et al, 2021 ). By conducting pharmacological network construction and molecular docking experiments on XG‐1, Wu et al screened out rutinum as one of the high‐efficiency targets (Wu et al, 2021 ), which docked to ACE2 and 3CLpro (Wu et al, 2021 ).…”
Section: Natural Products That Target Protein Of Sars‐cov ...mentioning
confidence: 99%
“…In China’s drug intervention program against COVID‐19, prescription XG‐1 has shown good treatment effects (Wu et al, 2021 ). By conducting pharmacological network construction and molecular docking experiments on XG‐1, Wu et al screened out rutinum as one of the high‐efficiency targets (Wu et al, 2021 ), which docked to ACE2 and 3CLpro (Wu et al, 2021 ). Tien’s group designed a more hydrophobic analog of rutin (Rutin‐M) to enhance its target ability to 3CLpro in an aqueous solution (Huynh, Wang, Cornell, & Luan, 2020 ).…”
Section: Natural Products That Target Protein Of Sars‐cov ...mentioning
confidence: 99%